2010
DOI: 10.1111/j.1476-5381.2010.00799.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemin‐enhanced expression of haem oxygenase‐1 stabilizes erythrocyte‐induced vulnerable atherosclerotic plaques

Abstract: Background and purpose:Previous studies demonstrated that intraplaque haemorrhage increased the contents of cholesterol and oxidants in atherosclerotic plaques. The present study was aimed to test the hypothesis that enhanced expression of haem oxygenase-1 (HO-1) may stabilize vulnerable plaques. Experimental approach: Intravascular ultrasound (IVUS) was performed to identify three similar abdominal aortic plaques in each of 58 fat-fed New Zealand rabbits after aortic balloon injury. With the guidance of IVUS,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
1
7
0
Order By: Relevance
“…In these two studies, the authors used Snprotoporphyrin 9, another HO-1 inhibitor, to show the anti-atherosclerosis effects of HO-1. Recently, Lin et al demonstrated that hemin-induced upregulation of HO-1 could stabilize vulnerable plaques (26). Our data are in agreement with these results.…”
Section: Discussionsupporting
confidence: 83%
“…In these two studies, the authors used Snprotoporphyrin 9, another HO-1 inhibitor, to show the anti-atherosclerosis effects of HO-1. Recently, Lin et al demonstrated that hemin-induced upregulation of HO-1 could stabilize vulnerable plaques (26). Our data are in agreement with these results.…”
Section: Discussionsupporting
confidence: 83%
“…This experimental model has now been reproduced for exploring the relationship between erythrocyte accumulation and oxidative stress. 52 , 53 The pathogenicity of cholesterol crystals is linked to their ability to rupture biological membranes, 54 to erode the thin cap, 55 and to protrude within the lumen inducing luminal thrombosis 56 and possibly embolism. Lastly, cholesterol crystals within vascular cells at the early stage of atheroma could trigger the inflammatory response.…”
Section: Biological Consequences Of Intraplaque Haemorrhagesmentioning
confidence: 99%
“…Appropriate isotype controls (negative control) were performed at the same concentrations as the primary antibodies. Immunohistochemically, (a) detection of neovessels was performed with a monoclonal mouse anti-rabbit CD34 antibody (CBL555, dilution 1:500, Chemicon International, CA, USA); (b) smooth muscle cells (SMC) were detected with a monoclonal mouse anti-rabbit α-actin antibody (HHF, dilution 1:400, Chemicon International, CA, USA); (c) macrophages were stained with a monoclonal mouse anti-rabbit RAM-11 antibody (M063, dilution 1:100, Dako, North America Inc., CA, USA); (d) intraplaque erythrocyte membranes (necrotic core) were visualized against biotin-conjugated Bandeiraea simplicifolia isolectin B4 (IB4) (L2140, dilution 1:200, Sigma Aldrich, MI, USA) [9]. …”
Section: Methodsmentioning
confidence: 99%